Entrepreneurs Riding the Wave of Circularity - UN Trade; Development (United Nations, 2024)
The publication explores the importance of moving towards a circular economy model — a growing economic model that not only tackles pressing environmental challenges but also has the potential to unlock economic growth, job creation, and contribute to building resilient and sustainable societies. The core focus of the publication within this topic lies in highlighting the pivotal role of entrepreneurs as catalysts of circularity. It emphasizes how entrepreneurs driving SMEs and start-ups have the power to bring about mindset changes within their communities and send ripples of change throughout the entire value chain by introducing new products, services, methods of production, and business models that respond to emerging needs. The paper also acknowledges the challenges that limit entrepreneurial innovation for a circular economy, particularly in developing nations. As such, it outlines policy measures to create a thriving environment for entrepreneurs to innovate in this direction.